Lambe-Lambe Theater: an immersion in the tiny world of the imagination (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
This work addresses theater in animated forms, more specifically the Lambe-Lambe Theatre, delving into the world of this recent language of animation.  The research provides a brief historical contextualization of the antecedents of animation and optical devices. It also addresses the emergence of street photographers, the origin of the Lambe-Lambe Theatre, its 30 years of existence and its relationship with the street.
Keywords: animated theater; theater of animated forms; Lambe-Lambe Theater; street theater; passerby